Vertical profiling of Saharan dust with Raman lidars and airborne HSRL in southern Morocco during SAMUM - Tesche, Matthias; Ansmann, Albert; MüLLER, Detlef; Althausen, Dietrich; Mattis, Ina; Heese, Birgit; Freudenthaler, Volker; Wiegner, Matthias; Esselborn, Michael; Pisani, Gianluca; Knippertz, Peter (Milton Park : Taylor & Francis, 2017)
Three ground-based Raman lidars and an airborne high-spectral-resolution lidar (HSRL) were operated duringSAMUM 2006 in southern Morocco to measure height profiles of the volume extinction coefficient, the extinction-to-backscatter ratio and the depolarization ratio of dust particles in the Saharan dust layer at several wavelengths. Aerosol Robotic Network (AERONET) Sun photometer observations and radiosoundings of meteorological parameters complemented the ground-based activities at the SAMUM station of Ouarzazate. Four case studies are presented. Two case studies deal with the comparison of observations of the three ground-based lidars during a heavy dust outbreak and of the ground-based lidars with the airborne lidar. Two further cases show profile observations during satellite overpasses on 19 May and 4 June 2006. The height resolved statistical analysis reveals that the dust layer top typically reaches 4–6 km height above sea level (a.s.l.), sometimes even 7 km a.s.l. Usually, a vertically inhomogeneous dust plume with internal dust layers was observed in the morning before the evolution of the boundary layer started. The Saharan dust layer was well mixed in the early evening. The 500 nm dust optical depth ranged from 0.2–0.8 at the field site south of the High Atlas mountains, Ångström exponents derived from photometer and lidar data were between 0–0.4. The volume extinction coefficients (355, 532 nm) varied from 30–300Mm−1 with a mean value of 100Mm−1 in the lowest 4 km a.s.l. On average, extinction-to-backscatter ratios of 53–55 sr (±7–13 sr) were obtained at 355, 532 and 1064 nm. publishedVersion